Determining Frequency of Multiple Organ System Involvement and Concurrent Lesions Identified in Feedyard Mortalities and Potential Associations with Cattle Demographics - Madeline R. Mancke; Brad J. White; Eduarda M. Bortoluzzi; Brandon E. Depenbusch; Paige H. Schmidt; Rachel E. Champagne; Makenna Jensen; Phillip A. Lancaster; Robert L. Larson (Veterinary Sciences, 2025)
Necropsies are commonly used to diagnose the causes of death in feedyard cattle, but the documentation of multiple organ system involvement and concurrent lesions is limited. This observational study aimed to determine the frequency of such findings and their associations with animal demographics. Systemic necropsies were conducted for 889 cattle mortalities with minimal autolysis across six feedyards in the Central High Plains during the summers of 2022 and 2023. Lesions and abnormalities were recorded along with arrival weight, sex, days on feed (DOFs), and number of treatments. The results showed that 72% of mortalities had more than one gross lesion, averaging 2.3 lesions per animal. The most common organ systems affected together were digestive and pulmonary (19%), followed by cardiovascular, digestive, and pulmonary (6%), and cardiovascular and pulmonary (5%). Common concurrent lesions included bronchopneumonia with an interstitial pattern (BIP) and gastrointestinal lesions (GI) (8%), bronchopneumonia and GI (7%), and acute interstitial pneumonia (AIP) and GI (3%). A generalized linear mixed effects model revealed that the likelihood of multiple lesions increased with DOFs (p = 0.02). These findings highlight the value of thorough necropsy documentation to enhance our understanding of disease and guide improved feedyard management and treatment practices.